2017
DOI: 10.1007/s11523-017-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PD-1/PD-L1 Immune Checkpoint in EGFR-Mutated or ALK-Translocated Non-Small-Cell Lung Cancer

Abstract: Immune checkpoint inhibitors, notably antibodies targeting programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1), have modified the management of patients with locally advanced or metastatic non-small-cell lung cancer (NSCLC). Several PD-1/PD-L1 inhibitors have been approved by health authorities for this indication and others are in clinical development. However, only a subset of patients truly benefits from these agents. For patients with mutated EGFR or translocated ALK NSCLC, for whom an immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 67 publications
0
76
1
Order By: Relevance
“…In this context, the use of ICIs remains controversial for patients harboring EGFR mutation and resistance to TKIs. Several studies have suggested that tumors with genetic EGFR/ALK alterations respond less well to ICI therapy than tumors without genetic EGFR/ALK alterations . The present study revealed that genetic EGFR/ALK alterations were associated with RP in the univariate analysis, although this association disappeared in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 52%
“…In this context, the use of ICIs remains controversial for patients harboring EGFR mutation and resistance to TKIs. Several studies have suggested that tumors with genetic EGFR/ALK alterations respond less well to ICI therapy than tumors without genetic EGFR/ALK alterations . The present study revealed that genetic EGFR/ALK alterations were associated with RP in the univariate analysis, although this association disappeared in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 52%
“…In our analysis, patients with EGFR mutations and/or ALK rearrangement had shorter OS. Retrospective analyses suggest lower PD‐L1 expression, and tyrosine kinase inhibitor (TKI)‐mediated inhibition of the PD‐1 axis in patients with ALK‐ and EGFR‐positive mNSCLC may lead to inferior outcomes . Additionally, these patients generally receive PD‐1 inhibitors in a later line of therapy, following progression on a TKI and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, patients with EGFR mutations and/or ALK rearrangement had shorter OS. Retrospective analyses suggest lower PD-L1 expression, and tyrosine kinase inhibitor (TKI)-mediated inhibition of the PD-1 axis in patients with ALK-and EGFRpositive mNSCLC may lead to inferior outcomes [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Furthermore, it has been predicted that lung adenocarcinoma could remain a major health problem for at least the next 50 years. 5 However, as it is a highly heterogeneous disease, the efficiency of targeted therapies is easily affected by compensatory changes of tumor tissues in response to different targeted therapies. 5 However, as it is a highly heterogeneous disease, the efficiency of targeted therapies is easily affected by compensatory changes of tumor tissues in response to different targeted therapies.…”
Section: Introductionmentioning
confidence: 99%